Discoid lupus erythematosus in an 8-year-old girl: A rare case - Febriani, Dina; Kusumawardani, Arie; Widhiati, Suci (Journal of General - Procedural Dermatology and Venereology Indonesia, 2023)
Background: The occurrence of discoid lupus erythematosus in children is uncommon. The global prevalence of childhood-onset SLE (cSLE) varies between 3.3 and 8.8 cases per 100,000 children. The objective of this article was to present a case of DLE in a child, aiming to establish a diagnosis, provide suitable management, and consider the potential risk of developing SLE. Case Illustration: An 8-year-old girl visited the polyclinic at Dr. Moewardi General Hospital complaining of reddish spots, scales with a black core, and a burning sensation on her cheeks and nose for three months. Initially, small pimples and reddish spots appeared on her face, which grew in size. A dermatological examination of the face showed partly hyperpigmented erythematous plaques, multiple well-defined scales, and partly merged plaques were observed. Discussion: In pediatric cases of DLE, the primary treatment approach involves minimizing exposure to UV radiation using sunscreen. Low-potency topical corticosteroids were administered on active lesions on the facial region. Systemic therapy may be considered, which may involve using immunomodulatory medications such as systemic corticosteroids and antimalarials. However, in this patient’s case, antimalarials were not given as clinical improvement was observed with topical corticosteroids. Conclusion: This case’s DLE diagnosis is based on the patient’s history, physical, and supporting examination. Education on risk factors and drug selection according to complaints is the key to successful therapy for DLE patients.